2010
DOI: 10.5042/bjfp.2010.0611
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of the implementation of the recovery philosophy in a secure forensic service

Abstract: a deeply personal, unique process of changing one's attitudes, values, feelings, goals, skills and/or roles. It is a way of living a satisfying, hopeful and contributing life even with the limitations caused by illness. Recovery involves the development of new meaning and purpose in one's life as one grows beyond the catastrophic effects of mental illness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 8 publications
(11 reference statements)
0
23
0
Order By: Relevance
“…Results demonstrated the need to ensure service users are helped to construct roles that meet the needs of their social environment and supports research on the importance of developing a coherent personal identity (Corlett & Miles, 2010;Maruna, 2001). Unless individuals can adopt an identity free of internalised stigma, they are at risk of returning to substance use.…”
Section: Recommendations and Conclusionmentioning
confidence: 69%
“…Results demonstrated the need to ensure service users are helped to construct roles that meet the needs of their social environment and supports research on the importance of developing a coherent personal identity (Corlett & Miles, 2010;Maruna, 2001). Unless individuals can adopt an identity free of internalised stigma, they are at risk of returning to substance use.…”
Section: Recommendations and Conclusionmentioning
confidence: 69%
“…Recovery in a forensic mental health context is often complicated by the offender‐patient's need to also recover from the consequences of their offence, which may include bereavement if he or she has killed a relative (Corlett and Miles, ; Simpson and Penney, ). In addition, such patients must embark on the process of recovery while facing restrictions on their autonomy and liberty – not only difficult in themselves, but also factors that perpetuate stigma, hopelessness and powerlessness (Corlett and Miles, ; Mezey et al, ; Livingston et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Available literature indicates that research on factors promoting personal recovery pathways among this population is particularly scant and most studies have measured relapse and reoccurrence of symptoms, applying a clinical approach to recovery. Research on personal recovery among offenders with mental illness showed that recovery is often accompanied by an additional process of 'offender recovery', as one has to rebuild a non-offender identity (Corlett & Miles, 2010;Drennan & Alred, 2014;Aga & Vanderplasschen, 2016). Consequently, recovery in this population is described as 'dual' or 'secure' recovery.…”
Section: Mental Health Care: the Emerging Recovery Movementmentioning
confidence: 99%